CURRENT ISSUE OF DISTANCE LEARNING - Toshpulatov Rakhimjon Ismailovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is aimed at solving the current problems of distance education today. Huge innovations introduced in the field of distance pedagogy over the years have raised a number of questions. The educational process in this field has undergone great changes. Every year, the number of information and communication technologies integrated into the field of education is increasing.